IMPROVING MECHANISMS FOR SHAPING THE ETHICS PRACTICES OF EDUCATIONAL INSTITUTION LEADERS THROUGH FORESIGHT TECHNOLOGY - Nurieva Umida Buribayevna; Baybayeva Muxayyo Xudaybergenovna (The Conference Hub, 2025)
In contemporary educational landscapes, ethical leadership plays a crucial role in guiding educational institutions toward sustainable development, fostering inclusivity, and maintaining academic integrity. However, the complex and rapidly changing environment in which educational institutions operate presents challenges in shaping and maintaining ethical practices. This paper explores how foresight technology can be leveraged to enhance the ethical practices of educational institution leaders. Foresight technology, encompassing tools and methods that help predict, analyze, and prepare for future trends and challenges, offers a unique approach to ethical decision-making. By integrating foresight techniques with ethical leadership development, educational institutions can better navigate ethical dilemmas, anticipate future ethical challenges, and build robust ethical frameworks. The paper outlines current challenges in ethical leadership, presents the potential of foresight technology, and suggests a framework for integrating foresight tools into ethical leadership practices.
Keywords: Ethical Leadership, Educational Institutions, Foresight Technology, Scenario Planning, Ethical Frameworks, Proactive Decision-Making, Stakeholder Engagement, Trend Analysis, Educational Sustainability, Accountability, Data Privacy, Artificial Intelligence in Education, Leadership Development, Environmental Scanning